1989
DOI: 10.1017/s0022215100108631
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of otitis media with effusion

Abstract: A study was undertaken to evaluate the prevalence and antibiotic susceptibility of bacteria present in the middle ear of patients with otitis media with effusion. Middle ear effusions (MEE), nasopharyngeal and throat swabs were obtained at operation and cultured for aerobic and anaerobic bacteria. Two hundred and fifty-nine effusions were obtained from 152 subjects examined.Haemophilus influenzaewas isolated from 32 (12.3 per cent) effusions.Streptococcus pneumoniaefrom seven (2.7 per cent),Staphylococcus aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Bacteriology of post-irradiated ear eVusion is rarely studied in the literature. Previous studies had conWrmed that bacteria were present in the middle ear in a signiWcant number of patients with non-irradiation related OME [19,20]. In contrast, most middle ear eVusion from our patients remained sterile.…”
Section: Discussionsupporting
confidence: 37%
See 1 more Smart Citation
“…Bacteriology of post-irradiated ear eVusion is rarely studied in the literature. Previous studies had conWrmed that bacteria were present in the middle ear in a signiWcant number of patients with non-irradiation related OME [19,20]. In contrast, most middle ear eVusion from our patients remained sterile.…”
Section: Discussionsupporting
confidence: 37%
“…Only 15 (17.6%) patients were free of OME, and one patient had a dry perforated eardrum. The resolution rate of OME in patients with pre-irradiated OME was lower than that of patients without pre-irradiated OME (0.71 vs. 19.7%). But there was no signiWcant diVerence in the resolution rates between patients with or without pre-irradiated OME (p = 0.447).…”
Section: Resultsmentioning
confidence: 70%
“…Several investigators [2,[8][9][10][11] have reported that at tacks of OME are due to impaired ventilation of the mid dle ear caused by eustachian tube dysfunction, inflamma tory components and infectious status. These previous studies of the relationship between attacks of OME and the nasopharyngeal bacterial flora suggested that the bac terial flora had some influence on attacks of OME occur ring via the eustachian tube.…”
Section: Discussionmentioning
confidence: 99%
“…In children with OME, high levels of pathogens, such as H. in fluenzae and S. pneumoniae, were detected and it was considered important to define the relationship between these strains and OME. However, almost all the reports [1][2][3][4] of strains detected in patients with OME were concerned with pathogens and few stud ies involved detailed investigations of the normal flora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation